Standardized in vitro bleeding tests in a non-coated novel hybrid prosthesis for frozen elephant trunk demonstrates minimal oozing during full heparinization, supported by clinical data - Jakob, Heinz; Leins, Timo; Avci-Adali, Meltem; Schlensak, Christian; Wendt, Daniel; Mehta, Yatin; Thielmann, Matthias; Görlinger, Klaus; Song, Suk-Won; Tsagakis, Konstantinos (Frontiers in Cardiovascular Medicine, 2023)
Introduction Recent reports have questioned the blood impermeability of the novel frozen elephant trunk (FET) device E-vita Open NEO© (EO-NEO). Therefore, standardized in vitro bleeding tests using porcine heparinized blood were performed, as well as stress testing on the blood tightness of the collar suture line, to investigate this observation. Material and methods EO-NEO prostheses were examined in vitro for blood permeability in three test series. Initially, antegrade perfusion with heparinized porcine blood [activated clotting time (ACT) of 500 s, with a 60 min duration] was performed, followed by ante/retrograde testing via the EO-NEO side port. Testing of the collar suture line under a tension of 10 Newton (N) within a suspension device (blood pressure 120 mmHg, ACT of 560 s, 1 min duration) was carried out with the suture material force fiber white (FFWs) yarn, using standard fixation (5 stitches/cm), FFWh yarn in hemostatic fixation (15 stitches/cm), and flow weave yarn (FWYh). Results Blood permeability testing of EO-NEO through the prosthetic lumen or via the side port demonstrated minor leakage without statistical difference between the standard and hemostatic suture lines or suture materials used, or positioning on the crimped or tapered portion (p > 0.05). The specific collar anastomosis testing demonstrated leakage volumes of 140 ml/min for FFWs vs. 16 ml/min for FFWh (p = 0.02), vs. 9 ml/min with the FWYh (p = 0.01). Conclusion Different blood leakage tests showed minimal oozing and no difference in blood loss through the fabric and different collar suture lines, but unphysiological pressurized retrograde perfusion of the collar region showed significantly less leakage using FWYh and FFWh, prompting production modification of EO-NEO. Clinical results confirmed low blood loss using this novel FET device.